Effect of Financing Risk and Liquidity Risk on Financial Performance in Islamic Commercial Banks in Indonesia - Biliyana; Erike Anggraeni; Liya Ermawati (Mutanaqishah: Journal of Islamic Banking, 2026)
Purpose– This study aims to analyze the effect of financing risk and liquidity risk on financial performance in Sharia commercial banks in Indonesia in 2020-2024. Methodology— This study uses a quantitative approach. Saturated sampling is a sampling method used by researchers. Therefore, there are 60 sets of financial statement data for the Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Return on Assets (ROA) in 2020-2024, which are used in this study. Findings – The results showed that financing risk consistently negatively and significantly impacted financial performance in both time periods, while liquidity risk was only negatively significant in the short term. However, these two risks have been shown to significantly influence financial performance in both the short and long term. Implications – Consistent and effective management of financing risk is crucial to the company’s financial performance in the short and long term. Liquidity risk requires special attention, especially for short-term financial stability, and both risks significantly impact the company’s performance across all periods. Originality—This study showed that financing risks persistently and significantly negatively affect financial performance across all time horizons, whereas liquidity risks affect performance only in the short term; collectively, these two risks remain the main determinants of financial performance.